PENGARUH PRODUK DAN LOKASI TERHADAP MINAT MENABUNG MASYARAKAT DI BANK SYARIAH INDONESIA KCP POLEWALI - Nurfitriani; Ulfa Hidayati (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2021)
Banks can be the people's choice in terms of saving for daily or future needs. The Muslim community can choose a seat that does not conflict with their Islamic teachings." Attraction is something that can experience pleasure, pleasure and relaxation. Products are anything that meets market needs and can be offered to the market for attention, purchase, use or consumption. This research uses a descriptive quantitative research type. in Polewali Regency using the intentional sampling method, Polewali district researchers collected 100 people as research samples and processed the data using the SPSS program. The variables used were product (X1), position (X2) and savings interest (Y). The data analysis technique used was descriptive data analysis, validity and reliability test, classical understanding test and hypothesis test. The output variable has a positive and significant effect on the public's interest in saving at Bank Syariah Indonesia Polewali. The calculated t value for this effect is 3.576 which is greater than the t table of 1.661, and this level of significance indicates that the greater public awareness of Islamic banking products and terms, the greater the interest in saving. The location variable has a positive and significant effect on the intention to save at Bank Syariah Indonesia Polewali with a t-count value of 3.879 with a t-table of 1.661 and a significant value of 0.000 <0.1.â€This shows that the ability of a location to influence public interest is directly proportional to the distance, security, reach, and the easily visible presence of a bank.â€Third, with F count 24.479 > F table 2.36 and a significance value of 0.000 <0.1, the product and location variables together have a positive and significant effect on people's interest in saving at Bank Syariah Indonesia Polewali. This means that if the product and location are further improved, the public's interest in saving will increase.â€